Good Good Father - Tomlin, Chris, 1972-; Barrett, Pat, 1984-; Hussey, Lorna (Nashville, Tennessee : Passion Publishing-Tommy Nelson, a division of Thomas Nelson Publishers, 2016)
"When his town is in trouble, a little bear named Tucker doubts why the King would have time for him and if he would really offer help. Just as Tucker is about to give up, the King runs to him offering love, acceptance, and help, assuring the reader that God truly is a Good Good Father and they are loved by Him"--
Keywords: God (Christianity) -- Love -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Bears -- Juvenile fiction; Animals -- Juvenile fiction; Christian life -- Juvenile fiction; God (Christianity) -- Love -- Fiction; Kings, queens, rulers, etc. -- Fiction; Bears -- Fiction; Animals -- Fiction; Christian life -- Fiction; Kings, queens, rulers, etc. -- Juvenile fiction; Animals -- Juvenile fiction